(untitled) (ACME, 2023)
This article analyzes the relationship between Pier Paolo Pasolini and the Bolognese Cineguf, during the years when he studied at the Liceo Galvani and then at the Facoltà di Lettere, under the guidance of such professors as Carlo Calcaterra and Goffredo Coppola. This research, based on a thorough examination of local newspapers and other documentary sources, not only deepens our knowledge of Pasolini’s film culture in the years of his youth, but also dates with greater certainty, to the early months of 1940, his first activities as a writer for the cinema, focusing on his Il giovine della primavera, which remained unpublished until 2001 and was then included in the Meridiani, edited by Walter Siti and Franco Zabagli. It is precisely this consideration of the activities of Cineguf as a whole that makes it possible to understand how much the life of that cultural circle influenced the poet’s passion for the silver screen, even prompting him to try his hand as a screenwriter.